High removal efficiency of antibiotic resistance genes in swine wastewater via nanofiltration and reverse osmosis processes. (1st February 2019) - Lan, Lihua; Kong, Xianwang; Sun, Haoxiang; Li, Changwei; Liu, Dezhao
Abstract: Swine wastewater treatment plant has become one of the main sources of antibiotic resistance genes (ARGs). Membrane treatment processes are promising solutions for removal of the emerging contaminants. However, limited studies have investigated the effects of nanofiltration and reverse osmosis treatment in removing ARGs in swine wastewater. In this study, the presence and the fate of common ARGs including sul 1, sul 2, tet A, tet M and tet W, as well as intI 1 and 16S rRNA gene, were investigated in a medium-sized (6500) pig farm wastewater treatment plant (WWTP) equipped with conventional biological treatment and advanced membrane processing system. All of the genes were detected with highly abundance in the raw sewage. The biological treatments of the swine wastewater treatment plant did not reduce the quantity of the ARGs. As expected, nanofiltration and reverse osmosis treatment reduced the absolute gene copy number of ARGs efficiently (4.98–9.52 logs removal compared to raw sewage). Compared to the reverse osmosis effluent, however, the absolute abundance of ARGs in the artificial wetland increased by 1.00–2.06 logs. Meanwhile, the relative abundance of sulfonamide resistant genes were basically unchanged, while tetracycline resistance genes ( tet A, tet M and tet W) decreased by 0.88, 3.47, 2.51 log, respectively. The results demonstrated that advanced membrane treatments are capable of removing various kinds of ARGs efficiently, as well as some common nitrogen and phosphorus contaminants. This study suggested a mature alternative method for the removal of ARGs from livestock wastewater. Graphical abstract: Image 1 Highlights: Swine sewage presents high content of ARGs. Nanofiltration and reverse osmosis reduces ARGs, nitrogen and phosphorus contaminants. The abundance of ARGs in artificial wetland increased.